Type specimens of vascular plants in the herbarium of the National Institute of Biological Resources (KB) of the Republic of Korea - Jang, Hyun-Do; Park, Jeong-Mi; Hyun, Chang-Woo; Lee, Byoung-Yoon; Noh, Tae-Kwon (Phytotaxa, 2020)
The article provides information on type specimens of 33 species (94 sheets) of vascular plants, kept in the herbarium of the National Institute of Biological Resources (KB) of the Republic of Korea. Most of the type specimens in KB were donated by the Herbaria of Ajou University (AJOU), Chonbuk National University (JNU), Chungbuk National University (CBU), Hallym University (HHU), Korea Plant Research Institute (KPRI), Seoul National University (SNU), and others in recent years. For all specimens, the type category is indicated. There were 15 sheets for holotypes, 57 sheets for isotypes, and 22 sheets for paratypes. There were seven species of Pteridophytes, 22 species of Dicotyledons, and four species of Monocotyledons. The most represented genera in the 33 species are Corydalis (seven species) and Isoetes (four species). The type specimens examined in this article belong to the taxa described by Korean botanists, Byoung-Un Oh, Byoung-Yoon Lee, Byung-Yun Sun, Chong-Wook Park, Hong-Keun Choi, Young-Dong Kim, and others.